DEVELOPING PLANT TOLERANCE INDICATOR TO AIR POLLUTION, CASE STUDY IN KRAKATAU INDUSTRIAL ESTATE CILEGON CITY, INDONESIA - Desi Anjana Dwiputri; Nizar Nasrullah; Zainal Alim Mas’ud (http://arl.faperta.ipb.ac.id/, 2018)
Plant tolerance against air pollutants from industrial estate can be assessed based on the change of physiological parameters calculated according to APTI (Air Pollution Tolerance Index by Singh). However, based on previous research, APTI formulation was less accurate, the results obtained between macroscopic and physiological observations are not always sync. Additional physiological parameters, i.e. total carbohydrates as main product of photosynthesis process was need to be examined. Therefore, purpose of this study were to examine the physiological parameters that indicate the level of tolerance of plants sensitivity to air pollution and to analyze the level of tolerance of tree species to air pollution in industrial estate. The method used in this research were survey method, along with macroscopic parameters (leaf area, leaf number, and leaf hue), microscopic parameters (stomatal density, leaf and palisade thickness) and physiological parameters (ascorbic acid content, total chlorophyll, leaf pH, water content, and total carbohydrate)observation of tree species which exposed to pollution and non-pollution (control). The results of this research showed that total carbohydrate as an additional parameter affected the level of tolerance by 49.2% and thus modified the APTI formulation and changed the classification range of plants tolerance. Results showed that the tolerant plants were Polyalthia longifolia Sonn.,Polyalthia fragrans (Dalzell) Hook. f. & Thomson, Erythrina crista-galli L., and Casuarina junghuhniana Miq.; moderate tolerance were Hibiscus tiliaceus L., Samanea saman (Jacq.)Merr. and Acacia auriculiformis A. Cunn. ex Benth; and intolerant were Leucaena leucocephala (Lam.) de Wit, Pterocarpus indicus Wild., and Swietenia mahagoni L.